The legitimacy of using dietary supplement diglycoside secoisolariciresinol (SDG) from flaxseed in cancer - Karolina Dobrowolska; Bożena Regulska-Ilow (National Institute of Public Health - National Institute of Hygiene, 2021)
Linseed, commonly known as flaxseed, is a fibre-rich food product. According to the recent study prepared by the American Institute for Cancer Research (AICR), an adequate intake of dietary fiber contributes to reducing the risk of colorectal cancer. In addition, the flaxseed and the oil extracted from it are considered to be food products with a high content of anti-inflammatory, unsaturated α-linolenic acid (ALA). However, the authors of the most recent scientific research have assigned the anticancer significance of flax seeds to plant lignan - secoisolariciresinol diglycoside (SDG), of which flaxseed is the main food source. This article provides a review of the world scientific literature together with an assessment of the validity of dietary supplementation with SDG from flaxseeds in cancer and during chemotherapeutic treatment. The paper also presents the European Food Safety Authority (EFSA) and the US Food and Drug Administration (FDA) view on dietary supplementation with flax seeds and its lignans. Additionally, selected dietary supplements available on the Polish market containing SDGs, linseed oil or linseed were analysed, together with a description of their intended use suggested by the manufacturers.